If social determinants of health are so important, shouldn't we ask patients about them?. (24th November 2020) - Moscrop, Andrew; Ziebland, Sue; Bloch, Gary; Iraola, Janet Rodriguez
Abstract : Patients' socioeconomic circumstances should be routinely documented in their healthcare record, say Andrew Moscrop and colleagues